(Mis)Brugen af Sylvia Likens: Fiktionaliseringer af et torturmord - Pedersen, Anne Bettina (Passage - Tidsskrift for litteratur og kritik, 2019)
Anne Bettina Pedersen: “(Mis)Using Sylvia Likens – Fictionalizations of a Torture-Murder” This article explores various fictionalizations of the 1965 torture and murder of Sylvia Likens. I examine a number of Sylvia Likens narratives and suggest that these texts reveal a specific pattern and a set of textual markers that identify them as Sylvia Likens narratives. The structures of Sylvia Likens texts mirror the torture methods used by her perpetrators and contribute to the continued (mis)use of her story and of her body.